Deficiency of vitamins C and E in women of childbearing age in Brazil: A systematic review and meta-analysis - Lucchetta, Rosa Camila [UNESP]; Cavicchioli, Sophia de Andrade [UNESP]; Gini, Ana Luísa Rodriguez [UNESP]; Forgerini, Marcela [UNESP]; Varallo, Fabiana Rossi [UNESP]; de Nadai, Mariane Nunes [UNESP]; Fernandez-Llimos, Fernando [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (FapUNIFESP (SciELO), 2021)
BACKGROUND: Despite the several options available for supplements containing vitamins C and E, evidence regarding the prevalence of deficiency or insufficiency of these vitamins is weak. OBJECTIVES: To estimate the prevalence of deficiency or insufficiency of vitamins C and E and associated factors among women of childbearing age, in Brazil. DESIGN AND SETTING: Systematic review and meta-analysis conducted at a Brazilian public university. METHODS: A search from index inception until May 2020 was conducted. Meta-analyses were performed using inverse variance for fixed models, with summary proportions calculation using Freeman-Tukey dou-ble arcsine (base case). Reporting and methodological quality were assessed using the Joanna Briggs Institute tool for prevalence studies. RESULTS: Our review identified 12 studies, comprising 1,316 participants, especially breastfeeding wom-en. There was at least one quality weakness in all studies, mainly regarding sampling method (i.e. conve-nience sampling) and small sample size. The prevalence of vitamin C deficiency ranged from 0% to 40%. Only vitamin E deficiency was synthetized in meta-analyses, with mean prevalences of 6% regardless of the alpha-tocopherol cutoff in plasma, and 5% and 16% for cutoffs of <1.6-12.0 mmol/l and < 16.2 mmol/l, respectively. The cumulative meta-analysis suggested that a trend to lower prevalence of vitamin E deficiency occurred in recent studies. CONCLUSIONS: Although the studies identified in this systematic review had poor methodological and reporting quality, mild-moderate vitamin C and E deficiencies were identified, especially in breastfeeding women. Thus, designing and implementing policies does not seem to be a priority, because the need has not been properly dimensioned among women of childbearing age in Brazil. REGISTRATION NUMBER IN PROSPERO: CRD42020221605.
Keywords: Hypovitaminosis; Lactating; Maternal nutrition; Nutritional epidemiology